BACILLUS MEGATERIUM BIODEGRADATION GLYCOPHATE - & et al., Mousa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to evaluate the Bacillus megatrium ability to growth and degradated the organophosphorus pesticides, Glyphosate. , Bacillus megaterium was isolated from Iraqi Soils and identification by morphological and biochemical tests beside a Sperber’s Medium as selectivity media. The best growth results were in (2- 60) days, had the same growth for both (5, 25) ppm on MSM. The best degradation rate ability % were in (25) ppm /60 days (70.9)%. The increasing in incubation show increasing of degradation ration% of Glyphosate  via HPLC specially after 60 days , the best ration were for (25)ppm .The result is the B. megaterium used the Glyphosate as source for carbon and phosphorus and suggest could be well exploited for bioremediation of Glyphosate contaminated sites.